Smart implants in fracture care – only buzzword or real opportunity?. (June 2021) - Ernst, Manuela; Richards, R. Geoff; Windolf, Markus
Highlights: Progression of fracture healing can be reliably measured by means of implant deformation in lower limbs. Smart sensor devices will be able to deliver such information through autonomous remote monitoring to support therapeutic decision making. Improved feedback on the healing progression holds the potential to accelerate recovery by more patient-specific fracture care. Abstract: The assessment of fracture healing is still marked by a subjective and diffuse outcome due to the lack of clinically available quantitative measures. Without reliable information on the progression of healing and uniform criteria for union and non-union, therapeutic decision making, e.g. regarding the allowed weight bearing, hinges on the experience and the subjective evaluation of physicians. Already decades ago, fracture stiffness has been identified as a valid outcome measure for the maturity of the repair tissue. Despite early promising results, so far no method has made its way into practice beyond clinical studies. However, with current technological advancements and a general trend towards digital health care, measuring fracture healing seems to regain momentum. New generations of instrumented implants with sensoring capabilities, often termed as "smart implants", are under development. They target X-ray free and timely provision of reliable feedback upon the mechanical competence of the repair tissue and the healing environment to support therapeutic decision making and individualized after-care. With the gained experience from these devices, the next generations of smart implants may become increasingly sophisticated by internally analyzing the measured data and suggesting adequate therapeutic actions on their own.